Evaluation of Safety and Efficacy with Propofol and Etomidate for Induction of Anaesthesia in Dilatation and Curettage - Kuwar , Bhaskar (Journal of Biomedical and Pharmaceutical Research, 2018)
Introduction and Aims: We compared the safety, efficacy, hemodynamic variation, recovery duration and adverse effects of propofol and etomidate, with or without fentanyl, in patients undergoing dilatation and curettage for incomplete abortions. Materials and Methods: One hundred patients, ASA status I & II, aged 20-50 years, undergoing dilatation and curettage, were randomly divided into four groups of 25 patients each. Group P received propofol 2 mg/kg + normal saline 2 ml for anesthesia induction. Group PF received propofol 2 mg/kg +fentanyl 1mcg/kg to make volume 2 ml for anesthesia induction. Group E received etomidate 0.2 mg/kg + normal saline 2 ml for anesthesia induction and Group EF received etomidate 0.2 mg/kg + fentanyl 1 mcg/kg to make volume 2 ml for anesthesia induction. Heart rate, arterial pressure and SpO2 were recorded at different time intervals. Therecovery time, pain on injection, myoclonus and postoperative nausea vomiting were also recorded. Results: During induction, mean arterial pressure fall significantly in both propofol groups. Amongst four groups, there was no significant difference observed in recovery time after anesthesia. The incidence of pain on injection was lower in etomidate groups. Myoclonus and Postoperative nausea and vomiting were significantly higher in etomidate groups. Conclusion: This study demonstrates that etomidate is superior in term of hemodynamic stability and less incidence of pain on injection. Etomidate combined with low dose fentanyl is more favourable than etomidatealone for attenuating myoclonus.